Empirical Formula for the Fundamental Period of Reinforced Concrete Moment Resisting Frames in Indonesia - Ilham Nurhuda; Parang Sabdono; Muhammad Ryan Afrizal; Laurensius Alvin Prima Pratama; Salman Ahmad Faishal (Jurnal Teknik Sipil, 2025)
Abstract